Analysis of Forms of Collaboration between Islamic Religious Education Teachers and Students' Parents - Puri Khoirunas; Siti Noor Mawar A. Rahman (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2023)
Purpose of the study: The purpose of this study is to find out and analyze what collaboration is carried out between Islamic religious education teachers and parents in instilling character values in students, and identify the constraints in carrying out collaboration between Islamic religious education teachers and parents. Methodology: Methods of data collection in this study using observation, interviews, and documentation. The data processing and analysis techniques go through three stages, namely data reduction, data presentation, and drawing conclusions. Main Findings: The results of the study showed that the forms of cooperation that existed between Islamic Religious Education teachers and parents varied, namely parenting classes, class forums, WhatsApp groups, contact books, direct meetings between teachers and parents, and home visits. The obstacle factors faced certainly vary in each collaboration carried out such as the absence of parents, the lack of understanding of parents in educating students, and the lack of openness from parents to teachers in problems faced by students. Novelty/Originality of this study: he learned about the novelty of this research about Collaboration Between Islamic Religious Education Teachers and Parents in Instilling Character Values in Students in Elementary Schools.